Study of Silver Nanoparticles Sensitized Fluorescence and Second-Order Scattering of Terbium(III)-Pefloxacin Mesylate Complex and Determination of Pefloxacin Mesylate - Aiyun Li; Zhiqiang Song (The Scientific World Journal)
α-Keto acid of pefloxacin mesylate (PFLX) can form the complex with Terbium(III). The intramolecular energy from PFLX to Terbium(III) ion takes place when excited, and thus Terbium(III) excited state is formed and then emits the characteristic fluorescence of Terbium(III), locating at 490, 545, 580, and 620 nm. The second-order scattering (SOS) peak at 545 nm also appears for the complex with the exciting wavelength of 273 nm. When the silver nanoparticles are added to the system, the luminescence intensity at 545 nm greatly increased. So, with the adding of nanoparticles to the Terbium(III)-PFLX complex, not only is the intramolecular energy promoted but also the SOS intensity is enhanced. The experimental results show that it is the silver nanoparticles with certain size and certain concentration which can greatly enhance the fluorescence-SOS intensity, and the relative intensity at 545 nm is proportional to the amount of PFLX. Based on this phenomenon, a novel method for the determination of PFLX has been developed and applied to the determination of PFLX in capsule and serum samples.